New model for complete design of rectangular isolated footings taking into account that the contact surface works partially in compression - Luévanos Rojas, Arnulfo (Revista ALCONPAT, 2023)
This paper shows a new model for complete design of rectangular isolated footings under uniaxial and biaxial bending, considering that the footing area in contact with the soil partially works to compression. The methodology is presented by integration to obtain moments, flexural shearing and punching shearing. Numerical examples are presented for design of rectangular isolated footings under uniaxial and biaxial flexion and are compared with the current model (total area works in compression) in terms of concrete and steel volumes. The current model shows greater volumes of concrete and steel. Therefore, the new model is the most appropriate, since it presents better quality control in the resources used.